Pelatihan Perencanaan Optimalisasi Sistem Lahan Pertanian Masyarakat Desa Kramat Kabupaten Lamongan - Rio Rahma Dhana; Armanda Lutfi Febrianto (Rengganis Jurnal Pengabdian Masyarakat, 2021)
Reservoir is a container or place for storing raw water, which will later be used as a temporary water storage area, then used as a place for water treatment for the continued growth of rice plants. In addition to rice plants, reservoirs are also used to minimize drought disasters in the dry season. The construction of this reservoir will be used by the Kramat village community to improve the economy in two sectors, namely agriculture and village potential, Kramat village itself is one of the villages in Lamongan Regency which has an area of ​​194.80 hectares and is located in Lamongan sub-district which has a population of 2,012 people. Most of their livelihoods are farmers. Seeing such conditions, farmers need facilities to help meet the needs of raw water for their agricultural land which will be planned with the planning method carried out by the construction of the reservoir with various stages such as measuring with 2 methods, either surveying in the field or utilizing digital applications or software using fields area or Google earth, after finding the size, then we can determine the sketch of the image on the reservoir by drawing in AutoCAD software. The area of ​​land used for the construction of the reservoir has an area of ​​1,452.03 m2, which is later estimated to be able to accommodate 8,507,190 L of water. The total volume of excavation work is 8,507.19 m3 with an estimated work period of 23 days. Excavator pc 200 heavy equipment operational cost : Rp. 101.200.000 per 23 days and for Dump truck capacity of 8 m3: Rp. 2,400,000 (2 dump trucks) per day.